Portfolio investments in Indonesia and Malaysia as examples of developing the investment attractiveness on Islamic capital markets - Broszkiewicz, Magdalena (Inwestycje portfelowe w Indonezji i Malezji jako przykład rozwoju atrakcyjności inwestycyjnej na islamskich rynkach kapitałowych, 2020)
The investment attractiveness of capital markets, e.g. the degree of distinction between regional and global markets, determines the ability to adapt to changing environmental conditions and information transparency. Market effectiveness as one of the pillars of the capital market is based on the stability and transparency of the legal framework that determines the possibilities of entering into a transaction. The main research goal of this article is the presentation of the inflow process of portfolio investment in Islamic countries, with a particular focus on the markets of Indonesia and Malaysia, in connection with their investment attractiveness. The strong interest in the capital markets of Islamic countries, especially after the financial crisis of 2008, has led to the dynamic development of these markets as well as the threat of the outflow of the so-called “hot capital”. The causes and effects of these processes are not sufficiently described in the literature
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 19-32
Keywords: capital market; portfolio investment; sharia; Indonesia; Malaysia; rynek kapitałowy; inwestycje portfelowe; szariat; Indonezja; Malezja